Digital storytelling on the iPad: Apps, activities and proceses for successful 21st century story creations - Ostashewski, Nathaniel; Reid, D. (AACE, 2012)
This paper presents action research examining the integration of digital storytelling using the iPad device in K12. The creation of digital stories is understood as one way to share student voice (author, 2011) and develop 21st century skills. The project goal was to bring storytelling to the K12 classroom in a manner that allowed for story sharing beyond the school building. Digital stories, created using software APPs allow for sharing online utilizing URLs. Research results indicate that in order to create meaningful stories, students need repeated practice opportunities with the iPad and apps. Another finding is that mobile devices with audio and image capture capabilities provide manageable ways for students to build stories. Constructionist activities, such as digital storytelling, can be made available to students, however require a simple workflow for successful implementation. Further research on kinds of software applications, processes, and teacher supports for successful implementation is needed.